ANALISIS TINGKAT KEPUASAN UNIT KEGIATAN MAHASISWA DAN ORGANISASI MAHASISWA TERHADAP PERAN LAYANAN KEMAHASISWAAN - Adryan Novanda; Annas Al Mudzakir; Nabilah Sri Rejeki (Program Studi Manajemen Pendidikan Islam, 2023)
The purpose of this study was to find out the role of student services and to analyze the satisfaction of UKM (Student Activity Units) and ORMAWA (Student Organizations) with the services provided by the student affairs bureau at Djuanda University, Bogor. This type of research is descriptive research with a mixed method approach. That is a combination of qualitative and quantitative research that is used together with the aim of obtaining more comprehensive, valid and objective data. The data collection technique used in this study was interviewing the head of the Djuanda University student bureau and completing a questionnaire by each head of the Student Activity Unit and Student Organizations at Djuanda University which would then be converted into qualitative information. The results of the study are described as follows: (1) Based on the results of the questionnaire analysis using a Likert scale, there is a total of 68.7% of respondents' satisfaction which illustrates that the level of satisfaction of the management of the Student Activity Unit and Student Organizations at Djuanda University is within category